Dynamics of vegetation structure and composition within early regeneration forest in the Danau Bangko Protected Area, Jambi, Indonesia - Asep Sadili; Dolly Priatna; Sutanto Sutanto (Indonesian Journal of Applied Environmental Studies, 2021)
An analysis of the growth dynamics of a 1-ha  (100 m x 100 m) permanent plot was carried out in the Danau Bangko Protected Area (DBPA) in March 2020. DBPA is part of the industrial plantation forest concession of PT Rimba Hutani Mas (PT RHM) in Jambi Province. The study aims to determine the dynamics of vegetation structure and composition between 2018 and 2020 in early regeneration forest. All trees tagged in 2018 were remeasured in 2020. Trees that had not been tagged previously but were 10 cm in diameter at breast height (DBH) were identified as a new recruit and tagged with a new number. Observations and data analysis were carried out on three stages of growth phases, namely in the tree phase ( 10 cm DBH), sapling phase (10 cm DBH), and seedling phase (height 1.5 m). The results showed that the number of species, genera, and families within the tree and sapling phases were high, but were low in the seedling phase. The dominant species in the tree phase in 2018,  Alseodaphne bancana,  had been  replaced by Archidendron bubalinum  in 2020, whereas the dominant species in the sapling phase (Rothmania sp.) and seedling phase (Aporusa microsphaera) remained the same from  2018  to 2020 . Mortality rates in all growth phases (tree, sapling and seedling) together is 4.67%. Recruitment into the tree phase from 2018 to 2020 was 2.67%,  consisting of eight species, eight genera, and seven families. Within one hectare permanent plot, all members of each tree species were distributed randomly. The vertical structure of the forest area is dominated by stratum C (4-20 m height). The results of hypothesis testing for each phase (tree, sapling, seedling) were different, however overall the results showed that the plot structure and composition had changed.Studi dinamika hutan dilakukan di Kawasan Lindung Danau Bangko (KLDB) pada Maret 2020 dengan menggunakan pendekatan plot permanen seluas satu hektar (100 m x 100 m). KLDB merupakan bagian dari konsesi hutan tanaman industri PT Rimba Hutani Mas (PT RHM) di Provinsi Jambi. Penelitian ini bertujuan untuk mengetahui dinamika struktur dan komposisi vegetasi antara pengukuran tahun 2018 dan 2020, khususnya pada areal dengan tutupan Belukar Tua (BT). Diameter semua pohon yang telah diberi tanda nomor pada tahun 2018 diukur kembali. Pohon yang belum diberi tanda sebelumnya tetapi diameternya 10 cm setinggi dada (DBH) ditetapkan sebagai rekrutmen baru dan diberi tanda dengan nomor baru. Pengamatan dan analisis data dilakukan terhadap tiga tahap tahap pertumbuhan, yaitu tingkat pohon (10 cm DBH), tingkat pancang (10 cm DBH), dan tingkat semai (tinggi 1,5 m). Hasil penelitian menunjukkan bahwa jumlah spesies, jumlah marga, dan jumlah famili pada tingkat pohon dan pancang tinggi, sedangkan pada tingkat semai rendah. Jenis dominan pada tingkat pohon pada tahun 2018 adalah Alseodaphne bancana telah digantikan oleh Archidendron bubalinum pada tahun 2020, sedangkan pada tingkat pancang (Rothmania sp) dan tingkat semai (Aporusa microsphaera) merupakan jenis yang dominan baik pada tahun 2018 maupun pada tahun 2020. Angka kematian pada semua tahapan pertumbuhan bervariasi dengan rata-rata 4,67%. Rekrutmen di tingkat pohon 2,67% yang terdiri dari 8 spesies, 8 marga, dan 7 famili. Secara keseluruhan, semua spesies tersebar secara acak. Tinggi tajuk pohon didominasi oleh stratum C (tinggi 4 m - 20 m). Hasil pengujian hipotesis pada setiap tingkatan (pohon, pancang, semai) berbeda, namun hasil penggabungan semua data menunjukkan bahwa telah terjadi dinamika.